PEMUTAKHIRAN DATA PROFIL DAN POTENSI DESA BERBASIS DATA DASAR KELUARGA - Neneng Yani Yuningsih; Iyep Saefulrahman (Lembaga Penelitian dan Pengabdian Masyarakat, 2020)
In village development, the availability of accurate village profile data has an impact on its consistency policy direction. However, there are some problems that are encountered to be able to update it including the quality of human resources, finance and infrastructure. Therefore, Community Service Program (PKM) activity is intended to provide knowledge about the importance of updating data in planning village development and helping the government update profile data and potential of their villages. The method used is training in updating basic data based on family data which is carried out by providing material and its implementation in the field. Community Service Program can be carried out according to the planned schedule, especially in the provision of training materials. Meanwhile, implementation of material in the training could not be carried out because it was constrained because lack of information technology. However, in general the Community Service Program in Neglasari Village was going well, marked by an increasing participant knowledge and an acceleration of online data updating assisted by students who were doing Community Service Program. Indirectly, this achievement at the same time show that the obstacles faced by Neglasari Village were not only on its human resources but rather on aspects of financial support and infrastructure. The actual presence from the government is needed to support the updating of the profile and potential data of this village because it is not only the village institution that requires it, but rather the central and regional governments.